The relationship between dietary inflammatory index in adults and coronary heart disease: from NHANES 1999–2018 - Xu, Hong; Xie, Pengxin; Liu, Hui; Tian, Zhenyu; Zhang, Ruitao; Cui, Ming (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have shown that pro-inflammatory diets increase the risk of coronary heart disease (CHD) and all-cause mortality. The dietary inflammatory index (DII) is a quantitative measure of dietary inflammation, and its accuracy has been validated by several studies.MethodsThis study included 43,842 participants aged ≥18 years from the National Health and Nutrition Examination Survey (NHANES) 1999–2018. The data of CHD was obtained through a questionnaire survey, and the DII was calculated using 24-h dietary recall data. Generalized linear models and logistic regression were used to determine the mediation factors, and subgroup analyses were conducted to evaluate the interaction between DII and CHD. Mean decrease in Gini (MDG) was used to determine the importance of individual dietary components.ResultsThe age of the participants was 49.81 ± 18.10 years, with 20,793 (47.4%) being male. A total of 1,892 (4.3%) participants were diagnosed with CHD, and the median DII score was 1.33 (0.11, 2.40). After adjusting for potential confounders, logistic regression analysis revealed that DII independently associated with CHD [OR: 1.049 (1.012–1.087), p = 0.008]. Triglyceride-glucose index, visceral adiposity index, body mass index, waist-to-height ratio, high-density lipoprotein, and glomerular filtration rate (all p < 0.05) may mediate the relationship between DII and CHD. Subgroup analyses showed that DII was more sensitive in participants aged <75 years (p < 0.001), females (p = 0.028), those with low cholesterol levels (p = 0.004), and individuals with low Framingham risk scores (p = 0.005). MDG analysis indicated that carbohydrate, vitamin C and iron intake have the greatest impact on CHD.ConclusionThis study suggests that various metabolic and lipid indicators play a mediating role in the relationship between DII and CHD. DII may have a greater adverse impact on traditional low-risk CHD populations.